2011
DOI: 10.1111/j.1365-313x.2011.04726.x
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RUGOSA2 encodes an mTERF family member required for mitochondrion, chloroplast and leaf development

Abstract: SUMMARYLittle is known about the mechanisms that control transcription of the mitochondrial and chloroplastic genomes, and their interplay within plant cells. Here, we describe the positional cloning of the Arabidopsis RUG2 gene, which encodes a protein that is dual-targeted to mitochondria and chloroplasts, and is homologous with the metazoan mitochondrial transcription termination factors (mTERFs). In the loss-offunction rug2 mutants, most organs were pale and showed reduced growth, and the leaves exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 92 publications
(179 reference statements)
4
105
0
Order By: Relevance
“…A retrograde signal from the chloroplast to the nuclei may be involved in this mechanism. Mutational analyses also indicate that mitochondrion-and/or chloroplast-dependent signals play roles in the development of leaf architecture in Arabidopsis (e.g., Wetzel et al 1994;Hricová et al 2006;Quesada et al 2011). But, even in plants treated with norflurazon, the onset of cell expansion in leaves is delayed although not cancelled (Andriankaja et al 2012), suggesting that other components are also important in the phase shift.…”
Section: Positive and Negative Regulators Of Cell Proliferation In Lementioning
confidence: 99%
“…A retrograde signal from the chloroplast to the nuclei may be involved in this mechanism. Mutational analyses also indicate that mitochondrion-and/or chloroplast-dependent signals play roles in the development of leaf architecture in Arabidopsis (e.g., Wetzel et al 1994;Hricová et al 2006;Quesada et al 2011). But, even in plants treated with norflurazon, the onset of cell expansion in leaves is delayed although not cancelled (Andriankaja et al 2012), suggesting that other components are also important in the phase shift.…”
Section: Positive and Negative Regulators Of Cell Proliferation In Lementioning
confidence: 99%
“…For example, the yellow and white sectors of variegated mutants had abnormal palisade cells [10,61,62] and an attenuated cell division and cell expansion response of palisade cells to excess light [63]. The green sectors of variegated leaves resembled wild-type leaves grown in optimal conditions [62] or resembled wild-type leaves exposed to excess light [64]. Additionally, immutans (im) had variegated leaves, attenuated biogenesis of non-photosynthetic plastids and short roots.…”
Section: Plastid Signals Contribute To Developmentmentioning
confidence: 99%
“…Thus, these mutant alleles were suggested to disrupt plastid-to-nucleus signalling mechanisms that contribute to leaf development [10,61]. For example, the yellow and white sectors of variegated mutants had abnormal palisade cells [10,61,62] and an attenuated cell division and cell expansion response of palisade cells to excess light [63]. The green sectors of variegated leaves resembled wild-type leaves grown in optimal conditions [62] or resembled wild-type leaves exposed to excess light [64].…”
Section: Plastid Signals Contribute To Developmentmentioning
confidence: 99%
“…The Arabidopsis genome encodes 35 mTERF proteins, and GFP fusion studies suggested that 11 of these are plastid localized, 17 are localized to mitochondria, while the localization of the remaining seven has not been determined (Babiychuk et al, 2011). Several plastid-localized mTERF proteins (At4g02990, BSM; At2g03050, SOLDAT10; At2g21710, EMB2219; At4g02990, RUGOSA2) have been genetically characterized in Arabidopsis; the null mutants have pale-green or embryo-lethal phenotypes with defects in plastid gene expression, but the precise molecular functions are unclear (Tzafrir et al, 2004;Meskauskiene et al, 2009;Babiychuk et al, 2011;Quesada et al, 2011). We identified 10 mTERF proteins in the maize nucleoid samples; eight of these have Arabidopsis orthologs based on reciprocal BLAST analysis, all of which were shown to be chloroplast localized in GFP fusion assays (Babiychuk et al, 2011).…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%